A phenomenological paradigm for empirical research in psychiatry and psychology: open questions - Irarrázaval, Leonor (Frontiers in psychology, 2020)
This article seeks to clarify the way in which phenomenology is conceptualized and applied in empirical research in psychiatry and psychology, emphasizing the suitability of qualitative research. It will address the What, Why, and How of phenomenological interviews, providing not only preliminary answers but also a critical analysis, and pointing to future directions for research. The questions it asks are: First, what makes an interview phenomenological? What are phenomenological interviews used for in empirical research in psychiatry and psychology? Second, why do we carry out phenomenological interviews with patients? Is merely contrasting phenomenological hypotheses or concepts enough to do justice to the patients’ involvement? Third, how should we conduct phenomenological interviews with patients? How can we properly perform analysis in empirical phenomenological research in psychiatry and psychology? In its conclusion, the article attempts to go a step beyond these methodological questions, highlighting the “bigger picture”: namely, the phenomenological scientific paradigm and its core philosophical claim of reality as mind-dependent.
Gesehen am 06.08.2020